The business occupier's handbook : a practical guide to acquiring, occupying, and disposing of business premises - Rubin, Vicky (E & FN Spon, 1997)
Presenting six steps on acquiring, occupying and disposing of business premises, this practical guide aims to assist businesses in protecting their interests, minimizing costs and maximizing the efficiency of their properties, in order to increase company profits.